Modelling the impact and cost-effectiveness of combination prevention amongst HIV serodiscordant couples in Nigeria. (24th September 2015) - Mitchell, Kate M.; Lépine, Aurélia; Terris-Prestholt, Fern; Torpey, Kwasi; Khamofu, Hadiza; Folayan, Morenike O.; Musa, Jonah; Anenih, James; Sagay, Atiene S.; Alhassan, Emmanuel; Idoko, John; Vickerman, Peter
<x xml:space="preserve">Abstract</x> Objective: To estimate the impact and cost-effectiveness of treatment as prevention (TasP), pre-exposure prophylaxis (PrEP) and condom promotion for serodiscordant couples in Nigeria. Design: Mathematical and cost modelling. Methods: A deterministic model of HIV-1 transmission within a cohort of serodiscordant couples and to/from external partners was parameterized using data from Nigeria and other African settings. The impact and cost-effectiveness were estimated for condom promotion, PrEP and/or TasP, compared with a baseline where antiretroviral therapy (ART) was offered according to 2010 national guidelines (CD4+ <350 cells/μl) to all HIV-positive partners. The impact was additionally compared with a baseline of current ART coverage (35% of those with CD4+ <350 cells/μl). Full costs (in US $2012) of programme introduction and implementation were estimated from a provider perspective. Results: Substantial benefits came from scaling up ART to all HIV-positive partners according to 2010 national guidelines, with additional smaller benefits of providing TasP, PrEP or condom promotion. Compared with a baseline of offering ART to all HIV-positive partners at the 2010 national guidelines, condom promotion was the most cost-effective strategy [US $1206/disability-adjusted-life-year (DALY)], the next most cost-effective intervention was to additionally give TasP to HIV-positive partners (incremental cost-effectiveness ratio US $1607/DALY), followed by additionally giving PrEP to HIV-negative partners until their HIV-positive partners initiate ART (US $7870/DALY). When impact was measured in terms of infections averted, PrEP with condom promotion prevented double the number of infections as condom promotion alone. Conclusions: The first priority intervention for serodiscordant couples in Nigeria should be scaled up ART access for HIV-positive partners. Subsequent incremental benefits are greatest with condom promotion and TasP, followed by PrEP.